Flame-retardant polycarbonate composition

By using a specific segmentation ratio of high molecular weight and low molecular weight polycarbonate, a combination of glass filler and phosphazene compounds in polycarbonate resins, the requirements of the polycarbonate resin composition in the prior art are difficult to meet the flame retardancy and mechanical properties in thin-walled structure applications, and a good balance between UL94 V0 flame retardancy and thermomechanical properties is achieved.

CN119630730APending Publication Date: 2025-03-14SABIC GLOBAL TECHNOLOGIES BV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380056066.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-27
Filing Date
2023-06-27
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Existing polycarbonate resin compositions are difficult to meet the requirements of flame retardancy, fluidity, rigidity and impact resistance in thin-walled structural applications, while the introduction of halogenated flame retardants may lead to reduced thermal stability and corrosion of molding equipment.

Method used

The use of expensive high-thermal polycarbonate copolymers is avoided by synergistic effects using flame retardant compositions containing 50 to 90% by weight of polycarbonate compositions, 5 to 30% by weight of glass filler and 3 to 10% by weight of phosphazene compound.

Benefits of technology

The flame retardant properties of UL94 V0 at 0.8mm are achieved, and at the same time, they have a good balance between thermal and mechanical properties, which is suitable for the manufacture of thin-walled structural parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005255874860000061
    Figure BDA0005255874860000061
  • Figure BDA0005255874860000071
    Figure BDA0005255874860000071
  • Figure BDA0005255874860000101
    Figure BDA0005255874860000101
Patent Text Reader

Abstract

The present invention relates to a flame retardant composition comprising, based on the weight of the composition: A. 50 to 90% by weight of a polycarbonate composition comprising, based on the weight of the polycarbonate composition, 15 to 85% by weight of a first polycarbonate and 85 to 15% by weight of a second polycarbonate, the first polycarbonate has a higher molecular weight than the second polycarbonate; b. 5 to 30 wt% of a glass filler; c. 4 to 10 wt% of a phosphazene compound; d. 0 to 10 wt% of other components; wherein the total amount of (A) to (D) is 100% by weight, and wherein the composition is selected to have a heat distortion temperature of at least 110 DEG C, preferably at least 120 DEG C, determined according to ISO 75 / A lay-flat mode at a load of 1.8 MPa, and a flame retardancy of V-0 at a sample thickness of 0.8 mm when tested according to the UL-94 protocol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a flame retardant (FR) composition comprising a blend of two polycarbonates, one of the polycarbonates having a higher molecular weight than the other, a glass filler and a phosphazene compound. The present invention further relates to an article comprising or consisting of such a composition. Background Art

[0002] Polycarbonate compositions comprising (one or more) FR additives are known per se in the prior art. They can be used for interior or exterior automotive applications as well as electrical and electronic applications, such as handheld devices, such as mobile phones or tablets, laptops, monitors, data storage, etc., computers, (tele)communication applications, across other different fields and applications. Such applications may be consumer products and appliances, automotive lighting, automotive under-hood, electric vehicle applications, electrical components, electronic displays, energy storage and lighting applications.

[0003] In many of these applications, there is a trend towards parts that have, at least in part, relatively small wall thicknesses. Therefore, compositions for the manufacture of such applications require a set of optimized flow and mechanical properties, such as impact and stiffness in particular, while maintaining good flame retardancy, such as UL V0 rating in particular.

[0004] Various strategies for increasing the rigidity of polycarbonate resins have been examined, and the strategy of incorporating fiber reinforcements, such as glass fibers, has been the most effective in responding to the need for high rigidity in thin-walled constructions. The introduction of halogenated flame retardants into polycarbonate resins has been used as a means of imparting flame retardancy to such glass fiber reinforced polycarbonate resins. However, polycarbonate resin compositions into which halogenated flame retardants containing chlorine, bromine, or fluorine are introduced exhibit reduced thermal stability and may cause corrosion of screws and molding tools in molding equipment during molding operations.

[0005] Glass fiber reinforced polycarbonate resin compositions having introduced organic phosphates such as phosphazenes are often used as an alternative strategy to existing prior art (see, for example, JPH1046017A, JPH1030056A, JP2006176612A and EP2810989B1). However, it is difficult to meet the current requirements for thin-wall flame retardancy using resin compositions having introduced organic phosphate esters FR. In addition, the inventors have found that the compositions of the prior art may not have the desired combination of rheological, mechanical and flame retardant properties. Therefore, there is a strong need for a polycarbonate resin composition that exhibits excellent balance between flame retardancy and fluidity, rigidity, impact resistance and heat resistance.

[0006] US2018 / 0142079 discloses a flame retardant composition comprising 20 to 80 weight percent of a polycarbonate; and 1 to 20 weight percent of a halogenated phenoxyphosphazene flame retardant, wherein all weight percentages are based on the total weight of the flame retardant composition.

[0007] US2021 / 0095118 discloses a glass-filled polycarbonate composition comprising 5 to 95 weight percent of a high heat copolycarbonate component having a glass transition temperature of 170°C or greater as determined in accordance with ASTM D3418 at a heating rate of 20°C / min; a phosphorus-containing flame retardant present in an amount effective to provide about 0.2 to 0.9 weight percent added phosphorus based on the total weight of the phosphorus-containing flame retardant; 5 to 45 weight percent glass fiber; optionally, 5 to 50 weight percent of a homopolycarbonate having a weight average molecular weight of 15,000 to 40,000 g / mole as measured via gel permeation chromatography using a bisphenol A homopolycarbonate standard, and wherein each amount is based on the total weight of the glass-filled polycarbonate composition and the sum thereof is 100 weight percent; wherein a molded sample of the glass-filled polycarbonate composition has a weight average molecular weight of 15,000 to 40,000 g / mole as measured in accordance with ISO 306 has a measured Vicat softening temperature greater than or equal to 135°C and a flame test rating of V0 measured in accordance with UL-94 at 1.0 mm thickness. Summary of the invention

[0008] In view of the foregoing, an object of the present invention is to provide a thermoplastic composition having a desirable combination of thin-wall FR performance, impact resistance, stiffness and flowability, which allows it to be suitable for the manufacture of thin-wall structural parts.

[0009] This object is at least partially achieved according to the present invention, which relates to a flame retardant composition comprising, based on the weight of the composition:

[0010] A. 50 to 90 weight percent of a polycarbonate composition comprising 15 to 85 weight percent of a first polycarbonate and 85 to 15 weight percent of a second polycarbonate, based on the weight of the polycarbonate composition, the first polycarbonate having a higher molecular weight than the second polycarbonate;

[0011] B. 5 to 30 wt % glass filler;

[0012] C. 3 to 10% by weight of a phosphazene compound;

[0013] D. 0 to 10% by weight of other components;

[0014] wherein the total amount of (A) to (D) is 100% by weight, and

[0015] Wherein, the composition is selected to have:

[0016] a heat distortion temperature of at least 110° C., preferably at least 120° C., measured in accordance with ISO 75 / A in a flat position at a load of 1.8 MPa, and

[0017] - Flame retardancy of V-0 at a sample thickness of 0.8 mm when tested according to UL-94 protocol.

[0018] The present inventors have found in particular that, compared to some compositions disclosed in the prior art, the use of expensive polycarbonate-polysiloxane copolymers or high heat polycarbonate copolymers can be avoided if a synergistic effect is used, which is achieved when using a polycarbonate composition having a specific ratio of split between high molecular weight and low molecular weight polycarbonate together with a phosphazene compound and a glass filler. A flame retardant property of UL94 V0 at 0.8 mm can be obtained together with a good balance of thermal and mechanical properties. Without being bound by it, the inventors believe that the split ratio between high molecular weight and low molecular weight polycarbonate in the polycarbonate composition of the present flame retardant composition is believed to be relevant to achieving this balance of properties.

[0019] The present invention will now be described in more detail.

[0020] Polycarbonate (PC)

[0021] Two different techniques are usually used to make aromatic polycarbonates. In the first technique, which is called the interfacial technique or interfacial process, phosgene is reacted with bisphenol, typically bisphenol A (BPA) in the liquid phase. Another well-known technique is the so-called melt technique, sometimes also called melt transesterification or melt polycondensation technique. In the melt technique or melt process, bisphenol, typically BPA, is reacted with carbonate, typically diphenyl carbonate (DPC) in the melt phase. It is known that the aromatic polycarbonates obtained by the melt transesterification process are structurally different from the aromatic polycarbonates obtained by the interfacial process. In this regard, it is particularly noted that the so-called "melt polycarbonate" typically has a minimum amount of Fries branches, which are generally not present in "interfacial polycarbonates". In addition, melt polycarbonates typically have a higher number of phenolic hydroxyl end groups, while the polycarbonates obtained by the interfacial process are typically end-capped and have a phenolic hydroxyl end group of at most 150 ppm, preferably at most 50 ppm, and more preferably at most 10 ppm.

[0022] The composition of the present invention comprises as component (A) 50 to 90% by weight of a polycarbonate composition comprising 15 to 85% by weight of a first polycarbonate and 85 to 15% by weight of a second polycarbonate, based on the weight of the polycarbonate composition. The amount of the first polycarbonate is preferably 25 to 75% by weight, more preferably 35 to 65% by weight, based on the weight of the polycarbonate composition. The amount of the second polycarbonate is preferably 75 to 25% by weight, preferably 65 to 40% by weight, based on the weight of the polycarbonate composition.

[0023] Preferably, the polycarbonate composition comprises at least 80 wt %, preferably at least 90 wt %, more preferably at least 95 wt % and even more preferably at least 99 wt % of the first and second polycarbonates, based on the weight of the polycarbonate composition. It is therefore preferred that the polycarbonate composition consists essentially of or consists of the first and second polycarbonates. The polycarbonate composition may contain additional polycarbonates, but preferably does not contain additional polymer components that are not polycarbonates.

[0024] The first polycarbonate and the second polycarbonate can have a weight average molecular weight of 25,000 to 60,000 daltons, provided that the first polycarbonate has a higher molecular weight than the second polycarbonate. Preferably, the first polycarbonate has a weight average molecular weight of 45,000 to 65,000 daltons, preferably 50,000 to 60,000 daltons, as measured by gel permeation chromatography using polystyrene standards. The second polycarbonate can have a weight average molecular weight of 25,000 to less than 45,000 g / mol, preferably 30,000 to 40,000 g / mol, as measured by gel permeation chromatography using polystyrene standards.

[0025] Preferably, the polycarbonate composition comprises at least two bisphenol A polycarbonates or is composed of at least two bisphenol A polycarbonates, and more preferably the polycarbonate composition is composed of at least two bisphenol A polycarbonates. Therefore, it is preferred that both the first polycarbonate and the second polycarbonate are bisphenol A polycarbonate homopolymers. In one aspect, the polycarbonate composition comprises two interfacial polycarbonates or is composed of two interfacial polycarbonates. In another aspect, the polycarbonate composition comprises two molten polycarbonates or is composed of two molten polycarbonates. In another aspect, the polycarbonate composition comprises a mixture of an interfacial polycarbonate and a molten polycarbonate or is composed of a mixture of an interfacial polycarbonate and a molten polycarbonate. The polycarbonate composition according to the present invention preferably does not include one or more polycarbonate-polysiloxane copolymers or one or more poly (carbonate-siloxane) copolymers, such as those within the meaning of US2021 / 0095118. More generally, the polycarbonate composition preferably does not include any polycarbonate copolymer. The polycarbonate composition further preferably does not include a high heat copolycarbonate component having a glass transition temperature of 170°C or above as measured according to ASTM D3418 at a heating rate of 20°C / min. More specifically, the polycarbonate composition preferably does not include a high heat copolycarbonate component, the high heat copolycarbonate component comprising a poly(carbonate-bisphenol phthalate) comprising 1-50 wt% of aromatic carbonate units and 50-99 wt% of bisphenol phthalate units, each based on the sum of the weights of the carbonate units and the bisphenol phthalate units; or a high heat copolycarbonate comprising an aromatic carbonate unit derived from 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethyl-cyclohexane, N-phenylphenolphthalein bisphenol , 4,4'-(1-phenylethyl)bisphenol, 4,4'-(3,3-dimethyl-2,2-dihydro-1H-indene-1,1-diyl)diphenol, 1,1-bis(4-hydroxyphenyl)cyclododecane, 3,8-dihydroxy-5a,10b-diphenylcoumarin-2',3',2,3-coumarin or a combination thereof, preferably 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, N-phenylphenolphthalein bisphenol or a combination thereof, and optionally a low heat aromatic carbonate unit, preferably a bisphenol A carbonate unit; or a combination thereof.

[0026] It is further preferred that the polycarbonate composition as disclosed herein does not comprise non-aromatic polycarbonates in addition to the aromatic polycarbonates.

[0027] The polycarbonate composition preferably has a melt volume rate (MVR) measured according to ISO 1133 (300° C., 1.2 kg) of 1 to 50 cc / 10 min, in particular 2 to 30 cc / 10 min.

[0028] The polycarbonate composition may also contain at least one polycarbonate resin regenerated from a used product (so-called recycled polycarbonate resin). Used products here can be exemplified by: optical recording media, such as optical discs; transparent vehicle parts, such as automobile window glass, automobile headlight lenses and windshields; containers, such as water bottles; eyeglass lenses; and building elements, such as soundproof walls, glass and corrugated panels. Rejected products; crushed materials obtained from, for example, gates and runners; and pellets obtained by melting the aforementioned can also be used. The recycled polycarbonate resin is preferably present in the flame retardant composition of the present invention at most 60% by weight and more preferably at most 40% by weight of the polycarbonate composition.

[0029] Glass filler

[0030] The glass filler (B) in the present invention is present in an amount of 5 to 30 wt %, preferably 8 to 20 wt %, more preferably 8 to 16 wt %, based on the weight of the composition. At these ratios, the rigidity of the composition of the present invention can be effectively improved due to the presence of the filler. The glass filler is at least one selected from glass fiber, glass flakes, ground glass fiber and glass beads, and preferably the glass filler is glass fiber.

[0031] Preferred are so-called E-glass fibers, also known as lime-aluminum-borosilicate glass. In order to achieve optimal mechanical properties, the glass fiber diameter is 6-20 microns, preferably 10-15 microns. In the preparation of the composition, it is convenient to use fibers in the form of chopped bundles with a length of 3 to 15 mm, although rovings can also be used. In articles molded from the composition, the fiber length is typically shorter due to fiber breakage during compounding or extrusion of the composition. The length of such short (i.e. shortened) glass fibers present in the final molded composition can be less than 4 mm. The glass fibers can be treated with a sizing agent to improve adhesion to the resin matrix. Preferred sizing agents include amino, epoxy, amide or mercapto functionalized silanes.

[0032] Phosphazene compounds

[0033] The phosphazene compound (C) used in the present invention is an organic compound having a -P=N- bond in the molecule. The amount of the phosphazene compound in the flame retardant composition is 4 to 10 wt%, preferably 5 to 7 wt%, based on the weight of the composition.

[0034] The phosphazene compound may have a structure represented by formula (I)

[0035]

[0036] Wherein R1 to R6 can be the same or different and can be an aryl group, an aralkyl group, a C1-12 alkoxy group, a C1-12 alkyl group or a combination thereof, and k is an integer from 1 to 10, preferably from 1 to 8. The phosphazene compounds according to structure (I) can be used alone or as a mixture. The residues R1 to R6 in structure (I) can be the same or different. The residues R1 to R6 of the phosphazene compounds of the present invention are preferably the same. In another preferred embodiment, only phosphazenes with the same residues R1 to R6 are used.

[0037] Preferably, the phosphazene compound comprises a cyclic phosphazene according to structure (I) having a proportion of oligomers (trimers) with k=1 of 50 to 98 mol %, preferably 70 to 90 mol % and more preferably 70-85 mol %.

[0038] The phosphazene compound may be selected from propoxyphosphazene, phenoxyphosphazene and methylphenoxyphosphazene. Preferably, the phosphazene compound comprises at least 50 wt% of phenoxyphosphazene, preferably 50 wt% to 100 wt% of phenoxyphosphazene, most preferably, the phosphazene compound consists of phenoxyphosphazene. In one aspect of the invention, the phosphazene compound comprises or consists of a phenoxyphosphazene according to structure (Ia), wherein k=1 and has an oligomer ratio of 50 to 98 mol%.

[0039]

[0040] The phosphazene compound according to the present invention preferably does not contain halogenated phosphazenes. In other words, the phosphazene compound is preferably a phosphazene compound that does not contain halogen. More specifically, the phosphazene compound preferably does not contain fluorinated phenoxyphosphazenes, such as trifluorophenoxyphosphazene.

[0041] Other components

[0042] The flame retardant composition according to the invention comprises 0 to 10% by weight of further components (D), based on the weight of the composition.

[0043] In particular, the other component (D) may comprise 1 to 5 wt% (based on the weight of the composition) of a flame retardant synergist selected from one or more of polysiloxane-polycarbonate copolymers, polysiloxanes, polyimides and polyetherimides. When the flame retardant synergist is added to the flame retardant composition, the flame retardant synergist promotes an improvement in flame retardant properties compared to a comparative composition containing the same amounts of all the same ingredients except the flame retardant synergist.

[0044] On the other hand, the other components according to the present invention may include 0.01 to 2 wt % of an anti-drip agent, based on the weight of the composition, which is preferably selected from one or more of PTFE and SAN-encapsulated PTFE.

[0045] In yet another aspect, the other components according to the present invention may comprise 0.01 to 3 wt % of one or more selected from talc, kaolin and mica, based on the weight of the composition.

[0046] Other components used in the composition may include one or more of lubricants and mold release agents (e.g., pentaerythritol tetrastearate), nucleating agents, stabilizers, antistatic agents (e.g., conductive carbon black, carbon fibers, carbon nanotubes, and organic antistatic agents such as polyalkylene ethers, alkyl sulfonates, or polyamide-containing polymers), acids, fillers, reinforcing materials (e.g., glass fibers or carbon fibers, mica, kaolin, talc, CaCO3, and glass flakes), dyes, and pigments.

[0047] Composition

[0048] The combination of specific types and amounts of materials constituting the flame retardant composition results in a distribution of properties, particularly in terms of FR performance, toughness, stiffness, and flowability. The examples and comparative examples disclosed herein provide the skilled artisan with materials that fall within and outside the scope of the invention, respectively, thereby forming a basis for developing additional embodiments according to the invention without undue burden.

[0049] According to the present invention, the flame retardant composition comprises, based on the weight of the composition:

[0050] A. 50 to 90 weight percent of a polycarbonate composition comprising 15 to 85 weight percent of a first polycarbonate and 85 to 15 weight percent of a second polycarbonate, based on the weight of the polycarbonate composition, the first polycarbonate having a higher molecular weight than the second polycarbonate;

[0051] B. 5 to 30 wt % glass filler;

[0052] C. 4 to 10% by weight of a phosphazene compound;

[0053] D. 0 to 10% by weight of other components;

[0054] However, the total amount of (A) to (D) is 100% by weight.

[0055] The amount of the polycarbonate composition (A) may be 60 to 90 wt%, more preferably 70 to 80 wt%.

[0056] The amount of glass filler (B) may be 8 to 20 wt%, more preferably 8 to 16 wt%.

[0057] The amount of the phosphazene compound (C) may be 5 to 7% by weight, more preferably 4 to 6% by weight.

[0058] The amount of the other component (D) may be 1 to 5% by weight, more preferably 1 to 3% by weight.

[0059] For the avoidance of doubt, the skilled artisan will appreciate that the total weight of the composition will be 100 wt % and that any combination of materials that do not total 100 wt % is unrealistic and not in accordance with the present invention.

[0060] Preferably, the polycarbonate composition (A) comprises at least 80 wt.-%, preferably at least 90 wt.-%, more preferably at least 95 or 99 wt.-% of the first and second polycarbonates, based on the weight of the polycarbonate composition. Preferably, the polycarbonate composition consists essentially of or consists of the first and second polycarbonates.

[0061] According to the present invention, the thermoplastic composition is selected to have

[0062] a heat distortion temperature of at least 110° C., preferably at least 120° C., as measured in accordance with ISO 75 / A flat method at a load of 1.8 MPa, and

[0063] - Flame retardancy of V-0 at a sample thickness of 0.8 mm when tested according to UL-94 protocol.

[0064] Preferably, the composition is selected to have a melt volume rate measured according to ISO 1133 (300°C, 1.2 kg) of at least 9.0 cc / 10 min, preferably from 10.0 to 20.0 cc / 10 min, more preferably from 12.0 to 16.0 cc / 10 min.

[0065] It is also preferred that the composition is chosen to have a tensile modulus measured according to ISO 527 at a temperature of 23°C of at least 3500 MPa, preferably from 3800 to 10000 MPa.

[0066] It is also preferred that the composition is selected to have a strength of at least 30 kJ / m 2 , preferably at least 70 kJ / m 2 , more preferably at least 130 kJ / m 2 , most preferably 135 to 170 kJ / m 2 Unnotched Izod impact strength measured according to ISO 180-1U at a temperature of 23°C.

[0067] Preferred ranges for the amounts of the components and preferred ranges for the properties of the composition may be combined without limitation, of course, as long as these ranges fall within the scope of the invention as defined herein in its broadest form. In other words, preferred ranges for one or more of the amounts and / or types of the components making up the thermoplastic composition may be combined with preferred ranges for one or more of the properties of the thermoplastic composition, and all such combinations are considered as disclosed herein.

[0068] The composition can be manufactured by various methods known in the art. For example, polycarbonate, glass filler, flame retardant additives and other additives are first blended in a high-speed mixer or by manual mixing. The blend is then fed to the throat of a twin-screw extruder via a hopper. Alternatively, at least one of the components can be directly fed into the extruder at the throat and / or downstream through a side feeder or introduced into the composition by being compounded into a masterbatch with a desired polymer and fed into the extruder. For example, a Krupp Werner & Pfleiderer ZSK2 co-rotating intermeshing 10-barrel twin-screw extruder with a diameter of 25 mm and an L / D ratio of 41 can be used to prepare the composition. The temperature in the extruder can be 180° C. to 265° C. along the screw length. The extrudate can be immediately cooled and granulated in a water bath. The pellets prepared in this way can be 0.6 cm or less in length as required. Such pellets can be used for subsequent molding, shaping or forming.

[0069] Also provided are formed, shaped or molded articles comprising the composition. The composition can be molded into articles by a variety of methods, such as injection molding, extrusion and thermoforming. Some examples of articles include articles for interior or exterior automotive applications and electrical and electronic applications, such as software products (mobile devices, laptops, monitors, tablets, data storage, etc.), computer and (tele)communication applications and across other different fields and applications, such as consumer products and appliances, automotive lighting, under the hood of automobiles, electric vehicle applications, electrical components, electronic displays, energy storage and lighting applications.

[0070] Therefore, the present invention relates to an article comprising or consisting of a composition disclosed herein. More particularly, the present invention relates to the manufacture of an article comprising or consisting of a composition disclosed herein, preferably an automotive component or an electrical or electronic component. Likewise, the present invention relates to a vehicle or an electrical or electronic device comprising said vehicle component or said electrical or electronic component.

[0071] The invention will now be further illustrated based on the following non-limiting examples.

[0072] Test Method

[0073]

[0074] Example

[0075] The samples were molded by injection molding on a L&T ASWA 100T injection molding machine set at 40 to 280° C. and the mold set at 80° C. The components of the compositions and their sources are listed in Table 1.

[0076] Table 1: Components of the composition and their sources

[0077]

[0078]

[0079]

[0080]

[0081] The amounts in Table 1 are weight percent based on the total weight of the composition. In all examples, the total amount of the components is equal to 100 weight percent. Table 1 shows that flame retardant compositions containing only one type of polycarbonate (CE1) or containing different FR compounds different from the phosphazene compounds of the present invention (CE2) or a weight percent of the phosphazene compounds lower than the claimed invention (CE3) do not conform to the claimed invention and do not show the desired flammability in terms of UL94 V0 at 0.8 mm.

[0082] However, the flame retardant compositions comprising polycarbonate compositions having a specific split ratio between high molecular weight and low molecular weight polycarbonate together with phosphazene compounds and glass fillers (E1 and E2) do show a good balance of flame retardant properties in achieving UL94V0 at 0.8 mm together with thermal and mechanical properties. It is believed that the split ratio between the high molecular weight and low molecular weight polycarbonate in the polycarbonate composition of the present flame retardant composition is related to achieving this balance of properties and UL94V0 at 0.8 mm. This is demonstrated in CE4, where the ratio of high molecular weight to low molecular weight polycarbonate is not in accordance with the present invention, and it has been found that UL94 V0 at 0.8 mm is not achieved, or the MVR is less than the desired range, or both. E3 and E4 demonstrate the effect of the present invention for higher concentrations of phosphazene compounds within the limits claimed.

[0083] It has also been demonstrated that similar properties are achieved when the composition comprises polycarbonates prepared by an interfacial process (E2 and E3) or by a melt process (E5 and E6). Examples E8 to E11 comprise a higher weight % of glass filler within the claimed limits together with the required weight % split of the two polycarbonates used in the present invention. All of these demonstrate the effectiveness of the present invention in achieving UL94 V0 at 0.8 mm together with a good balance of thermal and mechanical properties. In all experimental data (E1 to E11), it has been found that within the scope of the claimed invention, the composition exhibits the desired flammability properties (UL94 V0 at 0.8 mm). In all examples (E1 to E8), HDT, UNII and MFR are also within the acceptable range claimed by the present invention.

Claims

1. A flame retardant composition comprising, based on the weight of the composition: A. 50 to 90 weight percent of a polycarbonate composition comprising 15 to 85 weight percent of a first polycarbonate and 85 to 15 weight percent of a second polycarbonate, based on the weight of the polycarbonate composition, wherein the first polycarbonate has a higher molecular weight than the second polycarbonate; B. 5 to 30 wt % glass filler; C. 4 to 10% by weight of a phosphazene compound, preferably a halogen-free phosphazene compound; D. 0 to 10% by weight of other components; in, The total amount of (A) to (D) is 100% by weight, and Wherein, the composition is selected to have: a heat distortion temperature of at least 110° C., preferably at least 120° C., measured in accordance with ISO 75 / A in a flat position at a load of 1.8 MPa, and - Flame retardancy of V-0 at a sample thickness of 0.8 mm when tested according to UL-94 protocol.

2. The flame retardant composition according to claim 1, wherein the amount of the phosphazene compound is 5 to 7% by weight.

3. The flame retardant composition according to any one of claims 1 and 2, wherein the first polycarbonate has a weight average molecular weight of 45,000 to 65,000 g / mol, preferably 50,000 to 60,000 g / mol, as measured by gel permeation chromatography using polystyrene standards.

4. The flame retardant composition according to any one or more of claims 1 to 3, wherein the amount of the first polycarbonate is 25 to 75 wt%, preferably 35 to 65 wt%, based on the weight of the polycarbonate composition.

5. The flame retardant composition according to any one or more of claims 1 to 4, wherein the second polycarbonate has a weight average molecular weight of 25,000 to 45,000 g / mol, preferably 30,000 to 40,000 g / mol, measured by gel permeation chromatography using polystyrene standards.

6. The flame retardant composition according to any one or more of claims 1 to 5, wherein the amount of the second polycarbonate is 75 to 25 wt%, preferably 65 to 40 wt%, based on the weight of the polycarbonate composition.

7. The flame retardant composition according to any one or more of claims 1 to 6, wherein the polycarbonate composition comprises or consists of at least two bisphenol A polycarbonates.

8. The flame retardant composition according to claim 1, wherein the phosphazene compound has a structure represented by formula (I), wherein R1 to R6 may be the same or different and may be an aryl group, an aralkyl group, a C1-12 alkoxy group, a C1-12 alkyl group or a combination thereof, and k is an integer from 1 to 10, preferably from 1 to 8, 9. The flame retardant composition according to any one or more of claims 1 to 8, wherein the phosphazene compound comprises a phenoxyphosphazene.

10. The flame retardant composition according to any one or more of claims 1 to 9, wherein the glass filler is at least one selected from glass fibers, glass flakes, milled glass fibers and glass beads.

11. The flame retardant composition according to any one or more of claims 1 to 10, having a melt flow rate determined according to ISO 1133 (300°C, 1.2 kg) of at least 9.0 cc / 10 min.

12. The flame retardant composition according to any one or more of claims 1 to 11, further selected to have a tensile modulus of at least 3500 MPa, measured according to ISO 527 at a temperature of 23°C.

13. The flame retardant composition according to any one or more of claims 1 to 12, further selected to have a flame retardant strength of at least 30 kJ / m 2 , preferably at least 70 kJ / m 2 , more preferably at least 130 kJ / m 2 Unnotched Izod impact strength measured according to ISO 180-1U at a temperature of 23°C.

14. Article comprising or consisting of the flame retardant composition according to any one or more of claims 1 to 13.

15. Use of the flame retardant composition according to any one or more of claims 1 to 14 for the manufacture of articles, preferably automotive parts, electrical or electronic parts.

Citation Information

Patent Citations

  • Polycarbonate resin composition

    EP2810989B1

  • Flame retardant resin composition for cellular phone casings and cellular phone casing using it

    JP2006176612A

  • Flame retardant composition, methods of manufacture thereof and articles comprising the same

    US20180142079A1

  • Glass-filled flame retardant polycarbonate compositions and thin-walled articles thereof

    US20210095118A1